A critical role for the cholesterol‐associated proteolipids PLP and M6B in myelination of the central nervous system. Issue 4 (16th January 2013) - Werner, Hauke B.; Krämer‐Albers, Eva‐Maria; Strenzke, Nicola; Saher, Gesine; Tenzer, Stefan; Ohno‐Iwashita, Yoshiko; De Monasterio‐Schrader, Patricia; Möbius, Wiebke; Moser, Tobias; Griffiths, Ian R.; Nave, Klaus‐Armin
Abstract The formation of central nervous system myelin by oligodendrocytes requires sterol synthesis and is associated with a significant enrichment of cholesterol in the myelin membrane. However, it is unknown how oligodendrocytes concentrate cholesterol above the level found in nonmyelin membranes. Here, we demonstrate a critical role for proteolipids in cholesterol accumulation. Mice lacking the most abundant myelin protein, proteolipid protein (PLP), are fully myelinated, but PLP‐deficient myelin exhibits a reduced cholesterol content. We therefore hypothesized that "high cholesterol" is not essential in the myelin sheath itself but is required for an earlier step of myelin biogenesis that is fully compensated for in the absence of PLP. We also found that a PLP‐homolog, glycoprotein M6B, is a myelin component of low abundance. By targeting the Gpm6b‐gene and crossbreeding, we found that single‐mutant mice lacking either PLP or M6B are fully myelinated, while double mutants remain severely hypomyelinated, with enhanced neurodegeneration and premature death. As both PLP and M6B bind membrane cholesterol and associate with the same cholesterol‐rich oligodendroglial membrane microdomains, we suggest a model in which proteolipids facilitate myelination by sequestering cholesterol. While either proteolipid can maintain a threshold level of cholesterol in the secretory pathway that allows myelin biogenesis, lack of both proteolipids results in a severe molecular imbalance of prospective myelin membrane. However, M6B is not efficiently sorted into mature myelin, in which it is 200‐fold less abundant than PLP. Thus, only PLP contributes to the high cholesterol content of myelin by association and co‐transport. © 2013 Wiley Periodicals, Inc.